CD32a polymorphism rs1801274 affects the risk of Kawasaki disease - Zhiyong Wang; Pei-Liang Geng (Artificial Cells, Nanomedicine, and Biotechnology)
Aim To analyze the impact of CD32a polymorphism rs1801274 on the occurrence of Kawasaki disease (KD) through the meta-analysis.Methods The correlation between CD32a polymorphism rs1801274 and the susceptibility to KD was appraised using summarized odds ratios (ORs) with their 95% confidence intervals (95% CIs). Besides, stratification analyses were further implemented on the basis of ethnicity and control source, respectively. Between-study heterogeneity was checked adopting chi-square-based Q test, with p < .05 as significant level. And results from Q test determined which model would be employed for OR calculation, fixed- or random-effects. Sensitivity analysis was accomplished to test the stability of final results. Potential publication bias among included studies was investigated using Begg’s funnel plot and Egger’s test. If publication bias was significant, its influence on overall estimates would be measured adopting the trim-and-fill method.Results CD32a polymorphism rs1801274 significantly increased KD risk in total analysis under the comparisons of AA vs. GG, AA + AG vs. GG, AA vs. GG + AG, A vs. G and AG vs. GG (OR = 2.69, 95% CI = 1.39–5.20; OR = 2.00, 95% CI = 1.23–3.26; OR = 1.90, 95% CI = 1.23–2.94; OR = 1.77, 95% CI = 1.34–2.34; OR = 1.53, 95% CI = 1.07–2.19). After stratification analysis by ethnicity, similar tendency was also observed in Caucasian and Asian subgroups under corresponding genetic models. And parallel results were replicated in population-based and other-source subgroups after stratified analysis by control source, under some contrasts.Conclusion CD32a polymorphism rs1801274 has strong relation to KD onset, and the presence of its A allele could elevate the disease incidence.